Head Injury in Nepal: An Institutional Based Prospective Study on Clinical Profile, Management and Early Outcome of Traumatic Brain Injury in Eastern Part of Nepal - Kafle, Prakash; Khanal, Babita; Yadav, Dipak Kumar; Poudel, Deepak; Karki, Tejendra; Cherian, Iype (Birat Journal of Health Sciences, 2019)
Introduction: Traumatic brain injuries (TBI) are among the worst consequences and are the major causes of death and disability worldwide. It is considered as silent epidemics affecting individuals of all the ages and one of the major burden of neorological disease. Hence, TBIs are often overlooked and are sometimes called “the neglected disease of modern society”. Presenting GCS is the best predictor of outcome. Objective: The present study aims to portray the epidemiology, clinical profile, its management, early outcome and to evaluate the outcome predictors in a tertiary care center in eastern part of Nepal. Methodology: This is a prospective cross-sectional study conducted at the Department of Neurosurgery, Nobel Medical College Teaching Hospital, Biratnagar, Nepal over the period of 1 year (October, 2016 - December 2017). The primary objective of this study was to review the etiology, clinical profile and early outcome of patients with TBI. Results: During the study period, 1056 patients with head injuries were studied. Of these 202 cases required surgical intervention and 32 were excluded. Mean age of the study population was 38.7 years with the male to female ratio of 3.49:1. Road traffic accident was the most common cause of TBI (76%). Overall mortality rate was 11.17%. Unfavorable GOS at discharge was 43.5% and 26.1% at three months follow-up. Conclusion: TBI continues to be a significant burden of neurosurgical care in major neurosurgical centers in Nepal. This study contributes data on the etiology and clinical profile of patients with TBI from tertiary care center of Nepal.